2004
DOI: 10.1017/s0007123405000025
|View full text |Cite
|
Sign up to set email alerts
|

Men, Women and the Dynamics of Presidential Approval

Abstract: Although commentary on the 'gender gap' is a staple of political discourse in the United States, most analyses of the dynamics of presidential approval have ignored possible gender differences in the forces driving approval ratings of US presidents. This article analyses gender differences in the impact of economic evaluations and political interventions on the dynamics of presidential approval between 1978 and 1997. The analyses are made possible by disaggregating 240 monthly Survey of Consumers datasets gath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 2 publications
0
50
0
2
Order By: Relevance
“…Some survey studies focus explicitly on differences in economic expectations between women and men, finding that women are more pessimistic about the economy (Clarke et al, 2005). Smith and Powell (1990) show that among college graduates, men are also more likely to overestimate their future earnings.…”
Section: Literaturementioning
confidence: 99%
“…Some survey studies focus explicitly on differences in economic expectations between women and men, finding that women are more pessimistic about the economy (Clarke et al, 2005). Smith and Powell (1990) show that among college graduates, men are also more likely to overestimate their future earnings.…”
Section: Literaturementioning
confidence: 99%
“…Our research adds to the literature concerning gender and political attitudes, but it also contributes to a growing body of work on model heterogeneity (Bartle, 2005;Clarke et al , 2005). Advances in the study of voting have identified a variety of motivators of behaviour, but attempts to identify the sources, which drive these variations, have been somewhat lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Autores como Clarke, Stewart, Ault & Elliot (2005), tomando como caso de estudio a Estados Unidos, sostienen que muchos de los análisis de la aprobación presidencial han ignorado las posibles diferencias causadas por la variable género en la evaluación de los presidentes norteamericanos. De esta manera los autores analizan el impacto de la variable género en la evaluación de la economía y las dinámicas de la aprobación presidencial entre los años 1978 -1997.…”
Section: Aprobación Presidencial Y Sus Determinantes Una Revisiónunclassified